Translation and cultural adaptation of the Questionnaire on the Problematic Use of the Internet for the Peruvian population. - Otiura Trisano, Solange (2022)
Objective: To adapt the Problem Internet Use Questionnaire (PIUQ) for its utilization in Peru. Material and Methods: The translation and cultural adaptation of the PIUQ followed a systematic process that involved direct translation, evaluation and judgment by expert committees and back-translation, culminating with the final approval by the scale creators. For each of the 18 items, a first group of experts assessed comprehensibility, acceptability, relevance and quality of the response set in the preliminary version; subsequently, a second group of experts, evaluated clarity, relevance and pertinence in the final version. Aiken’s V was calculated for each of the different features evaluated in the 18 items. Results: In the preliminary version, Aiken’s V had low values for the comprehensibility of items 1, 3, 4, 6 and 16, and for the response set of item 4. The analysis of the first expert committee led to modifications in items 1, 4 and 16 of the obsession dimension, 5 and 8 of neglect, and 15 of control disorder. The evaluation by the second expert committee resulted in adequate Aiken V values for all aspects of the 18 items. Conclusions: The final Peruvian version thus obtained proved to be aligned to the purposes of the original questionnaire, without altering the meaning of the items.